Refereeing in sports is supposed to be a craft, not an art: response to Mascarenhas, Collins and Mortimer - Plessner, Henning; Betsch, Tilmann (Journal of sport & exercise psychology, 2002)
In their comments on a study on penalty decisions in soccer (Plessner & Betsch, 2001), Mascarenhas, Collins, and Mortimer (2002) point to several factors that, in their view, weaken the external validity of this laboratory study. In our response, we argue that although it may be helpful to substantiate the prior findings in a study closer to the natural setting of refereeing, Mascarenhas et al. provide no conclusive argument as to why the observed judgment biases should vanish under more realistic conditions.
Gesehen am 21.07.2022